Making the world over : confronting racism, misogyny, and xenophobia in U.S. history - Griffith, R. Marie (Ruth Marie), 1967- (Richard E. Myers lectures., 2021)
"Making the World Over examines the histories behind the issues at the root of our nation's conflicts both past and present, from race and immigration to misogyny and reproductive rights, in an attempt to encourage constructive dialogue"--